Kualitas Pelayanan Publik Untuk Menjaga Eksistensi Dalam Daya Saing Di Kantor Cabang Pos Aimas Kabupaten Sorong - Novitasari, Eka Indah; Kamaluddin; Muhdar, Aswad; Rumakat, Laila Qadriyani Malikin (Universitas Muhammadiyah Sorong, 2023)
Pos Indonesia is required to meet the needs of consumers, as well as become a level of measurement in the quality of the products provided with the aim of maintaining its existence. This research aims to determine the quality of service at the Aimas Post office as a formulation of service quality indicators and what factors encourage and inhibit the quality of public services. The method used is descriptive with qualitative data analysis. The technique for determining informants is through purposive sampling, and data collection techniques through observation, interviews, data sources and documentation. For data analysis techniques through data reduction, data presentation, as well as drawing conclusions and verification, and finally the validity of the data which will be carried out through credibility, transferability, reliability and confirmability tests. The results of the research show firstly, the level of service quality at the Aimas Post Office is almost entirely good, but there is a lack of dimensions in the supporting facilities at the Aimas Post Office. Second, the lack of factors driving service quality is the lack of an application or suggestion box at the Aimas Post office. Third, the inhibiting factor is the absence of intensive staff provision at the Aimas Post office.